A Panoramic View of Ferroptosis in Cardiovascular Disease - Xihao Cheng; Chao Yu; Xinquan Yang; Fudi Wang; Junxia Min (Karger Publishers, 2023)
Background: Cardiovascular disease (CVD) remains the leading cause of disease burden worldwide. Ferroptosis, an iron-dependent form of programmed cell death, is characterized by the lethal accumulation of lipid peroxidation, which is morphologically, biochemically, and genetically distinct from apoptosis, necrosis, and pyroptosis. Emerging evidence provides exciting novel insights to allow for a deeper understanding of the physiology and pathology of ferroptosis in CVD. Summary: The rapidly evolving insights into ferroptosis have revealed its role in the pathogenesis of diverse forms of CVD, including cardiomyopathy, heart failure, atherosclerosis, pulmonary arterial hypertension, and cerebrovascular disease. Various types of metabolic pathways are involved in the regulation of ferroptosis, including iron metabolism, lipid metabolism, and redox metabolism. Modulators of ferroptosis, such as several clinical drugs, preclinical compounds, and other emerging materials, have been applied as promising approaches in the prevention and treatment of CVD. Key Message: In this review, we provide a 360 degree view of the latest progress in the field of ferroptosis in CVD, highlight the pathogenic role of ferroptosis in CVD, and also discuss the importance and future directions of targeting ferroptosis in CVD.